PENILAIAN DAUR HIDUP BOTOL PET (POLYETHYLENA TEREPHTALATE) PADA PRODUK MINUMAN LIFE CYCLE ASSESSMENT (LCA) OF PET (POLYETHYLENA TEREPHTALATE) BOTTLES FOR DRINKING PRODUCT - Yani, Mohamad (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract The use of PET packaging in drinking products has increased and shifted glass packaging, so it is necessary to study the life-cycle of PET packaging. This research aims to evaluate life cycle of PET bottles on tea beverage products. This life-cycle assessment includes production process, inventory, environmental impact, and cost analysis. The life cycle of PET bottle in Indonesia is not complete. The relationship between PET bottle manufacturers, drinking manufacturers, and recycling waste, are unidirectional. The recycled waste-PET used for other products. Based on the analysis of inventory, PET bottles 600ml is nedeed 28g resin/ bottles and energy. The PET packaging production still produced a high defective product. Environmental impact assessment of PET bottle production indicates that the ambient air quality, noise and waste water are still good. The impact of PET bottle plant produce a global warming potential, reduce ozone layer and acid rain. The cost analysis describe that selling price of PET bottles is half the price of a glass bottle, while the price of waste- PET flake is three times higher than cullet. Although PET packaging is considered more practical, cheap and saving, but the recycling of PET packaging has not been widely utilized.
Keywords: Keyword: Life cycle assessment (LCA), PET, recycle, environmental impact